Association of Waist-Hip Ratio to Sudden Cardiac Death and Severe Coronary Atherosclerosis in Medicolegal Autopsies. (September 2017) - Kocovski, Linda; Lee, Joshua Dogyeong; Parpia, Sameer; Fernandes, John; Nair, Vidhya
Abstract : Abstract: Various modifiable and nonmodifiable risk factors, such as abdominal obesity, are known to affect the development of atherosclerotic cardiovascular disease and subsequent sudden cardiac death (SCD). The waist-hip ratio is a surrogate marker of visceral obesity that has been shown in various studies to be a better predictor of cardiovascular risk than the body mass index (BMI), a measurement of generalized obesity. Waist-hip ratio was measured prospectively on medicolegal autopsies performed for 1 year, in addition to standard measurements of BMI and heart weight, and histologic determination of severe coronary atherosclerosis (SCA, coronary artery diameter stenosis >75%). Logistic modeling was performed to determine any association between WHR, BMI, cardiovascular disease risk factors, heart weight, and SCD or SCA. Waist-hip ratio was not shown to be statistically significantly associated with either SCD ( P = 0.68) or SCA ( P = 0.14). Body mass index was shown to be significantly associated with SCA ( P < 0.001), and heart weight was shown to be significantly associated with both SCD and SCA ( P < 0.001, both). Waist-hip ratio, as a surrogate marker of central obesity and increased risk of atherosclerotic cardiovascular disease, is shown not to be statistically significantly associated with either SCD or SCA in postmortem cases.